Analysis of Iranian Muslim Gay Profile Uploads in @Thequeermuslimproject Instagram Account - Nara Garini Ayuningrum (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
Instagram as a new media offering free and global seems to be a means of